Analisis Perilaku Konsumsi Tomat oleh Rumahtangga Peserta Program Keluarga Harapan di Kota Pekanbaru - Amanda Zipora; Djaimi Bakce; Syaiful Hadi (Universitas Khairun, 2025)
Tomatoes (Solanum lycopersicum) are an important horticultural commodity that is widely cultivated and consumed in Indonesia due to their high nutritional content, including vitamin C, vitamin E, flavonoids, and lycopene. In addition to their economic value, tomatoes also play a role in fulfilling the nutritional needs of the community and are widely used as cooking ingredients as well as in herbal medicine. However, tomato price fluctuations often contribute to inflation in various regions, including Pekanbaru City. According to the Regional Inflation Control Team (2024), tomatoes are among the main commodities contributing to month-to-month inflation, recorded at 0.07 percent. This situation affects the purchasing power and consumption patterns of low-income households, particularly recipients of Program Keluarga Harapan (PKH). This study aims to analyze tomato consumption behavior and the factors influencing it among PKH households in Pekanbaru City. The research was conducted with 315 respondents using simple random sampling and multistage sampling methods, and the data were analyzed using multiple linear regression, elasticity analysis, and policy simulations. The results indicate that tomato prices, household income, and household size significantly affect consumption levels. Tomatoes were found to be price inelastic (–0.971) and classified as a normal good (income elasticity of 0.530).